FAKTOR RESIKO PENYEBAB PERDARAHAN POSTPARTUM DI PUSKESMAS PAMOTAN KABUPATEN REMBANG - Nurul Ummah; Ngadiyono Ngadiyono; Elisa Ulfiana (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
The Maternal Mortality Rate (AKI) in Indonesia is still high. According to SDKI in 2012 about 359 mothers died for every 100.000 babies born. The direct causes of maternal deaths in Indonesia as well as other countries are bleeding, infection, and eclampsia. From Puskesmas Pamotan's medical data records in 2015 from 437 woman who did labor, 51 of them experienced postpartum hemorrhage. The purpose of this study are to describe and analyze the factors that causing postpartum hemorrhage, especially in Puskesmas Pamotan. In this study we use analytic research method with retrospective case-control approach. Sampling Technique was used for cases group, while control group used simple random sampling. The result of this research showed that woman in risk age (20 or 35 years old) have 3.7 times greater risk of developing postpartum hemorrhage. Parity at risk (1 and 3) have 2.4 times greater risk of developing postpartum hemorrhage. Pregnant women with anemia (Hb 11) have 1.8 times greater risk of experiencing postpartum hemorrhage. And prolonged labor have 1.5 times greater risk of experiencing postpartum hemorrhage. It is sugessted that midwifes need to educate the public about the causes of postpartum hemorrhage. Woman should not be pregnant at too young or too old ages, the pregnant mother should do routine pregnancy checkups, and also give advice to Fertile Age Couples (PUS) to follow the Family Planning program (KB).